Magnitude of non-communicable disease screening and factors associated with awareness among reproductive age women in Gofa and Basketo zones, Southern Ethiopia: a community-based cross-sectional study - Domba, Markos Manote; Argefa, Terefe Gelibo; Gizaw, Abraham Tamirat; Bitew, Abewa Kebede (Frontiers in Global Women's Health, 2024)
BackgroundThe burden of non-communicable diseases (NCDs) increasing at an alarming rate in Ethiopia. NCDs affect reproductive-age women and cause significant threats to future generations. Screening is an important aspect leading to early diagnosis, treatment and preventing the risk of complications and future mortality. However, less attention has been paid in the post-pandemic era of COVID-19. Therefore, this study aims to assess awareness of NCD screening and associated factors among reproductive-age women in the Gofa and Basketo zones.MethodsA community-based cross-sectional study design was undertaken, employing a multistage cluster sampling method to select participants from the designated zones. Multivariate logistic regression was conducted using Statistical Package for the Social Sciences (SPSS) software. Associations were deemed statistically significant if the p-value was ≤0.05.ResultsThe awareness level for screening NCDs among women was found to be 54.8%. Specifically, the percentages for awareness of hypertension (HTN), diabetes, cervical cancer, and breast cancer screenings were 52.7%, 42.4%, 38.1%, and 34.8% respectively. However, the study revealed that only 43.0%, 9.4%, 16.2%, and 20.7% of the participants had undergone screening for HTN, diabetes, breast cancer, and cervical cancer respectively. High awareness of NCD screening was significantly associated with urban residence (AOR: 1.68, 95% CI: 1.63, 1.73), Gofa zone residence (AOR: 2.04, 95% CI: 1.95, 2.13), being able to read and write (AOR: 1.06, 95% CI: 1.02, 1.11), having primary (AOR: 1.13, 95% CI: 1.09, 1.16) and secondary school education (AOR: 1.11, 95% CI: 1.00, 1.14), being in the age group of 25–34 (AOR: 1.45, 95% CI: 1.41, 1.49) and ≥35 years (AOR: 1.22, 95% CI: 1.18, 1.26), being married (AOR: 1.25, 95% CI: 1.16, 1.35) and single women (AOR: 1.31, 95% CI: 1.18, 1.43), government employees (AOR: 1.65, 95% CI: 1.54, 1.77), having larger family sizes (>4) (AOR: 1.11, 95% CI: 1.05, 1.12) and having a family member diagnosed with NCD (AOR: 1.16, 95% CI: 1.11, 1.22).ConclusionsNearly half of the study population had no awareness of NCD screening and the vast majority had poor screening practice. Strengthening the provision of behavioral change communication strategies through trained health professionals based on the audience's segmentation by age, educational and economic status is needed.